Evolution of a geotechnical model for slope design in an active volcanic environment - Weir, FM; Fowler, MJ; Sullivan, TD; Kobler, M; Bu, J (Slope Stability 2020: Proceedings of the 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
The Lihir gold mine is located at the base of the amphitheatre of the Luise volcano, which is a young strata volcano that has undergone sector collapse, phreatomagmatic activity and alteration. This creates a geotechnically complex environment due to the co-incidence of complicated lithologies, alteration, structural, geothermal conditions, existing landslides and high seismicity. The rock mass model at Lihir comprises units that may be grouped into the following broad categories; surficial sediments, lithological and alteration. The structure model was developed understanding the geotechnically important strato-volcano regions which have been overprinted and modified by sector collapse and subsequent phreatomagmatic effects. The rock mass and structural understanding at Lihir are closely linked. Groundwater flow at Lihir is driven by the interplay of rainfall recharge, deep geothermal upflow and the ocean. Due to the elevated rainfall rates occurring in the area, recharge is significant across the entire site. The groundwater and geothermal conditions are complex and this makes pore pressure estimations for slope stability some of the most complicated undertaken in modern mining practices around the world. The geotechnical model comprises a view of the rock mass, structure and pore pressures. This paper presents the geotechnical model for pit slope design at Lihir gold mine with a focus on how our understanding of ground conditions and controls on slope stability has evolved over time.
Keywords: geotechnical model